SOLVING PROBLEMS OF APPLICATIONS OF COLLECTION THEORY (Academicia Globe: Inderscience Research, 2021)
In secondary schools, mathematics is studied on the basis of set theory. The article shows the importance of using the formulas of predicate algebra and set theory in solving mathematical problems. The issues raised here can be used not only to strengthen students' knowledge on the topic of collections, but also to organize math circle classes.